2017
DOI: 10.3892/mmr.2017.6178
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis on the differentiation of bone mesenchymal stem cells into osteoblasts and adipocytes

Abstract: The present study aimed to screen several differentially expressed genes (DEGs) and differentially expressed microRNAs (miRNAs) for two types of mesenchymal stem cell (MSC) differentiation. Bone morphogenetic protein 6 (BMP-6) and dexamethasone were used to induce MSCs towards osteoblastic differentiation or adipocytic differentiation. The t-test in the Bioconductor bioinformatics software tool was used to screen DEGs and differentially expressed miRNAs in the two samples. Subsequent gene ontology (GO) and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…By GO term analysis, our results showed that the hypermethylated DMGs were enriched in the mesenchyme development, mesenchymal cell differentiation, stem cell differentiation, skeletal system development, and so on, while the hypomethylated DMGs were enriched in cell fate commitment, and so on. Research has reported that cytoskeletal protein binding was enriched in the differentially expressed genes (DEGs) in the process of MSC osteogenic differentiation and adipocytic differentiation [ 28 ]. Other studies analyzed the dataset of hMSCs differentiated into osteoblasts and these studies report that skeletal development is a specific example of a heterogeneous GO class [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…By GO term analysis, our results showed that the hypermethylated DMGs were enriched in the mesenchyme development, mesenchymal cell differentiation, stem cell differentiation, skeletal system development, and so on, while the hypomethylated DMGs were enriched in cell fate commitment, and so on. Research has reported that cytoskeletal protein binding was enriched in the differentially expressed genes (DEGs) in the process of MSC osteogenic differentiation and adipocytic differentiation [ 28 ]. Other studies analyzed the dataset of hMSCs differentiated into osteoblasts and these studies report that skeletal development is a specific example of a heterogeneous GO class [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serine protease inhibitor A3 is likely involved in controlling elastase activity and members of this family have been implicated in maintaining barrier functions (Hu et al, 2013 ). Micro RNA 543 (mir543) has been associated with mesenchymal stem cell differentiation, and thus may be related to changes in the cellular differentiation pathways (Xu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results together provide strong evidence that upregulated ENAH performs an oncogenic role in multiple types of cancers including ESCC. Additionally, ENAH has been verified as a target of miR-495 and is associated with adipose cell differentiation in MSCs [32]. A previous study demonstrated that downregulated ENAH suppressed proliferation and migration of GC cells [33].…”
Section: Discussionmentioning
confidence: 97%